Kehadiran ikan invasif Nila Tilapia Oreochromis niloticus (Perciformes: cichlidae) di kepulauan Belitung, Indonesia - Hafidz, Agus Miftahudin; Vallen, Fitri sil (Universitas Batangahari Jambi, 2024)
The research was carried out aiming to report for the first time the presence of Oreochromis niloticus on Belitung Island (Indonesia), updating the invasion range of this species. The presence of non-native fish can have a negative impact on aquatic species communities through competition for resources, predation, hybridization, habitat modification, disease transmission (infection or parasitism), and genetic effects. We carried out an expedition to obtain O. niloticus specimens on January 20 and 25 2023, around six O. niloticus specimens were caught in the Lenggang River, Lenggang Village, Gantung District, East Belitung Regency, Belitung Island, Indonesia. Results from observations of meristic and morphological characteristics led to several specimens collected on Belitung Island being identified as Oreochromis niloticus. Discovery of O. Niloticus in the Lenggang River, as a new record representing the species' invasion range approximately 226 km to the east of Bangka Island. The discovery of this species contributes to understanding the extent of expansion and invasion of O. niloticus in Indonesia. This information is very important for classifying and determining river conservation strategies, as well as for planning efforts to protect ecosystems, especially from non-native species that have the potential to become invasive species.